2014
DOI: 10.1128/iai.02254-14
|View full text |Cite
|
Sign up to set email alerts
|

The Agr Quorum-Sensing System Regulates Fibronectin Binding but Not Hemolysis in the Absence of a Functional Electron Transport Chain

Abstract: Staphylococcus aureus is responsible for numerous chronic and recurrent infections, which are frequently associated with the emergence of small-colony variants (SCVs) that lack a functional electron transport chain. SCVs exhibit enhanced expression of fibronectin-binding protein (FnBP) and greatly reduced hemolysin production, although the basis for this is unclear. One hypothesis is that these phenotypes are a consequence of the reduced Agr activity of SCVs, while an alternative is that the lack of a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Intracellular residency places S. aureus beyond the reach of immune surveillance and some antibiotics, while a lack of Agr-mediated toxin production results in a weak inflammatory response [94,95]. This is exemplified by the emergence of small colony variants, which are strongly associated with chronic and recurrent infections and lack the ability to produce cytolytic toxins due to diminished Agr activity and a disrupted electron transport chain [95,96].…”
Section: Community-associatedmentioning
confidence: 99%
“…Intracellular residency places S. aureus beyond the reach of immune surveillance and some antibiotics, while a lack of Agr-mediated toxin production results in a weak inflammatory response [94,95]. This is exemplified by the emergence of small colony variants, which are strongly associated with chronic and recurrent infections and lack the ability to produce cytolytic toxins due to diminished Agr activity and a disrupted electron transport chain [95,96].…”
Section: Community-associatedmentioning
confidence: 99%
“…This phenomenon is not necessarily the result of a reduced concentration of the quorum-sensing peptide due to the reduced growth rate of the SCV (148). We (86) and Pader et al (167) showed that exogenous autoinducing peptide (AIP) is able to trigger RNAIII expresion in TD-SCVs (86) and in menadione-and hemin-dependent SCVs (167), thereby demonstrating that synthetic AIP is able to activate Agr in at least some SCVs. Based on cDNA libraries built from total RNA, which was collected from different growth phases of an S. aureus strain pair displaying both the normal and the SCV phenotype, phenotypespecific expression of non-protein-encoding RNAs (npcRNAs) was shown (168,169).…”
Section: Alterations In Electron Transport and Their Impact On Metabomentioning
confidence: 99%
“…These are all factors that interact or induce immune cell responses. Previous studies have shown that there is a quorum-sensing system, the accessory gene regulator (agr) system, in S. aureus, and this is central in the control of specific virulence factors (52)(53)(54). There have been studies that report mutations in the agr system and indeed mutations through the course of infection (54).…”
Section: Figmentioning
confidence: 99%